Collaborative governance of postgraduate medical education: Can it be achieved?. (2nd December 2021) - Herbert, Carol P.; Busing, Nick; Nasmith, Louise
Abstract: Faced with the need to modernize and improve the postgraduate medical education experience and to maintain the high quality of physicians that Canadians expect, in 2010, four organizations –Association of Faculties of Medicine of Canada (AFMC); Collège des Médecins du Québec (CMQ); College of Family Physicians of Canada (CFPC); and Royal College of Physicians and Surgeons of Canada (RCPSC) formed a consortium to conduct a review of Postgraduate Medical Education (PGME) in Canada. In 2012, the Consortium published the Future of Medical Education in Canada Postgraduate (FMEC PG) project's 10 recommendations for change in PGME. One of these recommendations was to 'Establish Effective Collaborative Governance in PGME'. The recommendation stated- 'Recognizing the complexity of PGME and the health delivery system within which it operates, integrate the multiple bodies (regulatory and certifying colleges, educational and healthcare institutions) that play a role in PGME into a collaborative governance structure in order to achieve efficiency, reduce redundancy, and provide clarity on strategic directions and decisions' The purpose of this paper is to describe the creation, function and dissolution of a collaborative governance structure within the complex system of PGME and the challenges that were faced in its sustainability. The lessons learned are applicable internationally where integration of multiple organizations is being attempted. A fundamental question remains as to whether a consensus-based decision-making process can ever be achieved among organizations with overlapping mandates and in some cases, hierarchical structures?